2019
DOI: 10.1111/jhn.12727
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a healthy diet enriched or not with pecan nuts or extra‐virgin olive oil on the lipid profile of patients with stable coronary artery disease: a randomised clinical trial

Abstract: BackgroundThe present study aimed to assess the effect of a healthy diet, enriched or not with pecan nuts or extra‐virgin olive oil, on the lipid profile of patients with stable coronary artery disease (CAD).MethodsThis was a randomised clinical trial conducted for 12 weeks with patients aged between 40 and 80 years with stable CAD for more than 60 days. Individuals were randomised into groups [control group (CG) with 67 patients, pecan nut group (PNG) with 68 patients and olive oil group (OOG) with 69 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 46 publications
3
35
0
4
Order By: Relevance
“…Furthermore, nut consumption has been related to lower IHD incidence [15]. Systematic reviews and metanalyses from randomized trials have shown the effects of different nuts and peanut intake on cardiometabolic features in primary cardiovascular prevention [16,17] but few clinical trials have been conducted in individuals with previous IHD [8,[18][19][20][21]. In addition, these studies show discrepancies in the results, possibly due to different sample sizes and differences in the dietary pattern adopted for both intervention and control groups, intervention duration, design, population, and type of nuts evaluated [8,[16][17][18][19].…”
Section: Background and Rationale {6a}mentioning
confidence: 99%
“…Furthermore, nut consumption has been related to lower IHD incidence [15]. Systematic reviews and metanalyses from randomized trials have shown the effects of different nuts and peanut intake on cardiometabolic features in primary cardiovascular prevention [16,17] but few clinical trials have been conducted in individuals with previous IHD [8,[18][19][20][21]. In addition, these studies show discrepancies in the results, possibly due to different sample sizes and differences in the dietary pattern adopted for both intervention and control groups, intervention duration, design, population, and type of nuts evaluated [8,[16][17][18][19].…”
Section: Background and Rationale {6a}mentioning
confidence: 99%
“…Rajaram et al (2001) mostraram perda de peso com uma dieta enriquecida com nozes-pecãs (20% do total de energia) durante quatro semanas em comparação com a outra dieta de estudo. Campos et al (2020) observaram redução do peso corporal e IMC no grupo das nozes-pecãs (30 gramas diárias por doze semanas), porém, sem diferença significativa em comparação aos outros grupos de estudo (óleo de oliva e controle).…”
Section: Discussionunclassified
“…Quatro ensaios clínicos anteriores ao nosso estudo, com duração de pelo menos 4 semanas, avaliaram os efeitos do consumo de noz-pecã nos lipídios sanguíneos (MORGAN;CLAYSHULTE, 2000;RAJARAM et al, 2001;MCKAY et al, 2018;CAMPOS et al, 2020). Morgan e Clayshulte (2000) ofertaram 68 gramas de nozes-pecãs durante oito semanas para adultos com níveis lipídicos normais, este grupo de intervenção mostrou uma diminuição do LDL da linha de base para a 4ª semana e também para a 8ª semana.…”
Section: Discussionunclassified
See 2 more Smart Citations